The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/polym12092048
|View full text |Cite
|
Sign up to set email alerts
|

High-Barrier Polyimide Containing Carbazole Moiety: Synthesis, Gas Barrier Properties, and Molecular Simulations

Abstract: A high-barrier polyimide (2,7-CPI) was synthesized through the polymerization of pyromellitic dianhydride (PMDA) and a novel diamine (2,7-CDA) containing carbazole moiety. The synthesized diamine and polyimide were fully characterized by elemental analyses, FTIR and NMR. The 2,7-CPI displays very attractive barrier performances, with oxygen transmission rate (OTR) and water vapor transmission rate (WVTR) low to 0.14 cm3·m−2·day−1 and 0.05 g·m−2·day−1, respectively. Meanwhile, 2,7-CPI also exhibits exceptional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“… a Units of (cm 3 (STP)·cm −3 ·cm Hg −1 ); b (10 −8 ·cm 2 ·s −1 ); c (10 −8 cm 3 (STP)·cm·cm −2 ·s −1 ·cm Hg −1 ); d Data comes from Ref. [ 56 ]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… a Units of (cm 3 (STP)·cm −3 ·cm Hg −1 ); b (10 −8 ·cm 2 ·s −1 ); c (10 −8 cm 3 (STP)·cm·cm −2 ·s −1 ·cm Hg −1 ); d Data comes from Ref. [ 56 ]. …”
Section: Resultsmentioning
confidence: 99%
“…Solubility coefficients, diffusion coefficients and permeability coefficients for H 2 O and O 2 in NAPPI and Kapton. Units of (cm 3 (STP)•cm −3 •cm Hg −1 ); b (10 −8 •cm 2 •s −1 ); c (10 −8 cm 3 (STP)•cm•cm −2 •s −1 •cm Hg −1 ); d Data comes from Ref [56]…”
mentioning
confidence: 99%
“…Unfortunately, the performance of commercial PI films, such as Kapton H® and Upilex S®, cannot meet the abovementioned requirement for flexible OLED substrates. Therefore, further improvement of T g and reduction of CTE have become hot research topics in the field of PI film materials 13–22 . Previous studies have shown that the intrinsic method, i.e., designing the molecular chain structure of PI, has the most obvious effect on the increase of T g and reduction of CTE 23–25 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, further improvement of T g and reduction of CTE have become hot research topics in the field of PI film materials. [13][14][15][16][17][18][19][20][21][22] Previous studies have shown that the intrinsic method, i.e., designing the molecular chain structure of PI, has the most obvious effect on the increase of T g and reduction of CTE. [23][24][25] Yang et al prepared a series of PI films with pyridine and pyrimidine structures.…”
Section: Introductionmentioning
confidence: 99%
“…Morpholinyl, hexafluoroisopropyl (C[CF 3 ] 2 ), pyridine heterocyclic and fluorene “cardo” pendant non coplanar structures were introduced into the main chain of polyimide to investigate the influence of chemical structure under nitrogen atmosphere, physical properties and gas transport properties tested by various characterization methods. In addition, molecular dynamics simulation has emerged as an important theoretical tool to characterize the structural characteristics and gas permeation performances of polyimides at the atomic level, which is difficult to achieve by experimental means 34,40 . And a detailed molecular simulation study was carried out by Materials Studio 9 to comprehensively explore the relationship between chemical structures, free volume and gas transport properties of polymers.…”
Section: Introductionmentioning
confidence: 99%